Factors influencing Intensive Care Units nurses in end-of-life decisions - Michelle Freire Baliza; Regina Szylit Bousso; Kátia Poles; Maiara Rodrigues dos Santos; Lucía Silva; Maria Cristina Paganini (SciELO, 2015)
OBJECTIVETo identify the factors that influence the Intensive Care Unit nurse in the decision-making process in end-of-life situations.METHODEthnographic case study, which used the theoretical framework of medical anthropology. Data were collected through semi-structured interviews with 10 nurses.RESULTSThe inductive thematic analysis enabled us to identify four themes:The cultural context of the Intensive Care Unit: decision-making in situations of end-of-life; Beliefs and subjectivity of care in end-of-life situations; Professional experience and context characteristics of end-of-life care situations; and Humanization practices in end-of-life situations: the patient and family centered care.CONCLUSIONProfessional maturity, the ability to transmit information and the ability to negotiate are directly related to the inclusion of nurses in the decision-making process.